EFEKTIVITAS EFFLEURAGE MASSAGE ABDOMEN TERHADAP PENURUNAN NYERI DISMENORE PRIMER PADA REMAJA PUTRI - Pangaribuan, Maslan (Jurnal Ayurveda Medistra, 2026)
Introduction: Primary dysmenorrhea is a menstrual disorder that is most often found in women, especially young women, the incidence of primary dysmenorrhea in Indonesia reaches around 54.89%. One way to overcome primary dysmenorrhea experienced by young women is abdominal effleurage massage which is a non-pharmacological therapy. The aim of the study: To determine the effectiveness of abdominal effleurage massage on reducing the pain intensity of primary dysmenorrhea in young women at the Ash-Sidiq Mosque in 2022. Research design: Pre-experimental (one group pretest and posttest design). The population: of all young women who have experienced menstruation at the Ash-Sidiq Mosque who attend the taklim assembly is 120 respondents. The sample of young women who experienced primary dysmenorrhea amounted to 37 respondents. The sampling technique was quota sampling. The instrument used standard operating procedures (SOP) and NRS questionnaire, bivariate analysis using paired samples T-test with a significance level of 0.05. Results: Pretest value of moderate pain intensity (4.70) and posttest value of mild pain intensity (1.59), the average decrease in dysmenorrhea pain scale is 3.11. Statistical test results of the value of Sig. 2-tailed = 0.000 where p<0.05. Conclusion: Abdominal effleurage massage is effective in reducing primary dysmenorrhea pain in young women.